Análisis De Las Exportaciones Colombianas De Petroleo Y Que Productos A Exportar Podrian Reemplazar El Deficit Que Se Va A Presentar En La Balanza De Pagos Por Las Restricciones Del Actual Gobierno Nacional A La Exportacion De Hidrocarburos (2023)
Analyze the impact that the restrictions imposed by the current government could have for the extraction and export of hydrocarbons (petroleum), and how the deficits that will be generated in the balance of payments due to said restrictions, giving a possible solution by exporting other products that replace hydrocarbons.